SWOT Analysis on PT. Bank Sumut Syariah Sub-Branch Binjai - Nia Andriani; Wahyu Syarvina (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
PT. Bank SUMUT Syariah Binjai Branch is one of the companies engaged in Islamic financial institutions. In carrying out activities as a company engaged in banking, it is necessary to carry out a SWOT analysis which aims to find out how deposit products are used. This SWOT analysis technique is applied to determine the company's goals. For this the company analyzes the existing strengths, weaknesses, opportunities and threats. This study uses qualitative methods to collect data in the form of descriptive data, both written and spoken language of the people and observed behavior. The results of this study are that 1). Strength in deposit products at PT. Bank SUMUT Syariah Binjai Branch is located on the ratio or profit sharing time deposits offered by deposits starting from 1 month, for a period of 1 month, customers will be given a profit sharing ratio of 60%. 2). The weakness lies in the bank's very strategic location and is not visible because it is squeezed with other buildings. 3). For customers who will withdraw their money, there will be no administrative fees and penalties will be imposed so that it can be used as a good opportunity for customers. 4). The threat lies in banking regulations which can change at any time sometimes become a threat, and conditions of intense competition.